The association between brain injury, perioperative anesthetic exposure, and 12‐month neurodevelopmental outcomes after neonatal cardiac surgery: a retrospective cohort study. Issue 3 (March 2014) - Andropoulos, Dean B.; Ahmad, Hasan B.; Haq, Taha; Brady, Ken; Stayer, Stephen A.; Meador, Marcie R.; Hunter, Jill V.; Rivera, Carlos; Voigt, Robert G.; Turcich, Marie; He, Cathy Q.; Shekerdemian, Lara S.; et al.
Summary Background Adverse neurodevelopmental outcomes are observed in up to 50% of infants after complex cardiac surgery. We sought to determine the association of perioperative anesthetic exposure with neurodevelopmental outcomes at age 12 months in neonates undergoing complex cardiac surgery and to determine the effect of brain injury determined by magnetic resonance imaging (MRI). Methods Retrospective cohort study of neonates undergoing complex cardiac surgery who had preoperative and 7‐day postoperative brain MRI and 12‐month neurodevelopmental testing with Bayley Scales of Infant and Toddler Development, Third Edition (Bayley‐III). Doses of volatile anesthetics (VAA), benzodiazepines, and opioids were determined during the first 12 months of life. Results From a database of 97 infants, 59 met inclusion criteria. Mean ± sd composite standard scores were as follows: cognitive = 102.1 ± 13.3, language = 87.8 ± 12.5, and motor = 89.6 ± 14.1. After forward stepwise multivariable analysis, new postoperative MRI injury (P = 0.039) and higher VAA exposure (P = 0.028) were associated with lower cognitive scores. ICU length of stay (independent of brain injury) was associated with lower performance on all categories of the Bayley‐III (P < 0.02). Conclusions After adjustment for multiple relevant covariates, we demonstrated an association between VAA exposure, brain injury, ICU length of stay, and lower neurodevelopmental outcome scores at 12 months of age. These findings support the need for further studies to identify potential modifiable factors in the perioperative care of neonates with CHD to improve neurodevelopmental outcomes.